Protocolo de uso de Albumina Humana al 20% - Herrera Comoglio, Raquel; Calantoni, Miguel Alberto; Galarza, S; Bosio Beatriz; Alesso, Luis; Villarreal, O; Rueda, María José; Soria, Gustavo; Kasparian, Andrés; Almaraz, C; Pucheta, M; Ojeda, Verónica; et al. (2021)
1 recurso en línea 3 p.